ANALISIS IMPLEMENTASI SAK ETAP MENJADI SAK EP: STUDI KOMPARATIF PERUSAHAAN MANUFAKTUR DAN JASA - Madaharsa, Abhyasa Sulthan; Muslimin, Muslimin (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This research aims to examine the effects of implementing the new financial accounting standard—Standar Akuntansi Keuangan Entitas Privat (SAK EP), or Financial Accounting Standards for Private Entities—on the financial reporting practices of two regionally owned enterprises (BUMD) in East Java: PT. Panca Wira Usaha Jawa Timur and PT. Karet Ngagel Surabaya Wira Jatim. Previously, both companies adopted the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) but have now begun transitioning to SAK EP, which will be mandatory starting January 1, 2025. This study offers a comprehensive summary of the changes and difficulties encountered during the transition using a qualitative research design and a multiple case study methodology. The findings show significant changes in the way financial aspects are recognized, measured, presented, and disclosed under SAK EP, especially with relation to deferred tax, employee benefits, asset revaluation, and impairment of inventory and receivables. The transition has necessitated updates to accounting information systems, capacity-building initiatives for staff, and the engagement of external consultants. The implementation of SAK EP is expected to enhance the accountability, relevance, and openness of financial reporting among Indonesian private enterprises, despite the significant financial and time costs.